THE EFFECTIVENESS OF NATIONAL AGENCY FOR COMBATING TERRORISM’S DERADICALIZATION PROGRAM TOWARD TERROR CONVICTS IN INDONESIA - Jerry Indrawan; M. Prakoso Aji (Indonesia Defense University, 2019)
Deradicalization programs have been implemented in Indonesia since 2012. This program employs preventive paradigm in implementing the policies it produces. During the seven years of implementation, deradicalization experienced challenges and obstacles. So far, there are many critics addressed to deradicalization program, such as criticism toward the lack of budget, prison facilities, deradicalization materials provided to terror convicts, post-deradicalization follow-up, as well as negative public reception on the idea of ex-terror convicts returning to society. These problems are hampering the effectiveness of deradicalization program. This paper employs theory of deradicalization and theory of effectiveness. It employs qualitative method with deductive and conceptual analysis, and the data is obtained through literature studies. This paper aims to see the effectiveness of deradicalization program carried out by National Agency for Combating Terrorism (BNPT) toward terror convicts in Indonesia.Keywords: Terrorism, Deradicalization, Terror Convicts, Resocialization and Reintegration